The Effect of Aerobic Exercise on the Muscle Stem Cells Fibers - Thuc, Dao Chanh (International Journal of Medical and Health Sciences Research, 2018)
Satellite cells are indispensable for skeletal muscle repair and regeneration and are associated with muscle growth in humans [1]. Aerobic exercise training results in improved skeletal muscle health also translating to an increase in satellite cell pool activation. We postulate that aerobic exercise improves satellite cell function in skeletal muscle.